Towards the Estimation of Demand for Recycling in Chile: The Case of Santiago - Vasquez-Perez, O (Elsevier, 2014)
In developing countries, the recycling of municipal solid waste (MSW) as an alternative to the traditional MSW management requires an economic sustainability valuation. From this perspective, the estimation of demand for recycling is crucial. In this paper, we study the case of recycling MSW in Santiago, Chile. We estimate the relation between the monthly amount of MSW separated voluntarily from apartments located in Santiago and the monthly price required to participate in a municipal recycling program. We consider the transference of the municipal cost savings to the owners of the apartments due to the amount of MSW separated for recycling, which is not collected and deposited in the current MSW system. For the estimation, we use concepts from environmental economics and psychology, analyzing the operation and municipal costs incurred by current MSW management and designing and applying a survey based on a contingent valuation method (CVM) approach. The results indicate that the percentage of MSW separated for recycling varies between a 27.98% and 33.18%, that only four MSW types are affected by a variation of the monthly price, and that a reduction of monthly collection trips in the current MSW system from 24 to 18 can be obtained. Additionally, we discuss a number of methodological aspects to be considered in a similar study of valuation of recycling in developing countries. Our conclusion is that Santiago has favorable conditions for the implementation of a recycling program as an alternative to the current MSW system. © 2013 Elsevier B.V. All rights reserved.
Keywords: Municipal solid waste management; Recycling; Demand; Contingent valuation method; Santiago de Chile